Perilaku Pencarian Informasi Pemustaka Berdasarkan Metode Penelusuran Informasi Khulthau - Fikri Aprialdi; Eka Nursah Pitri; Mifta Huljannah Sihombing; Umar Ariansyah Siregar; Franindya Purwaningtyas (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information seeking behavior is all the activities of a person or group in searching, finding, and using all information. Information search occurs when someone is aware of their information needs and then that person will do various ways so that their information needs are achieved, usually after finding the source of information they are looking for, the information will be implemented through action. Especially for users who are the most frequent objects in need of information to carry out their activities both from their work and social environment. The purpose of this study was to determine the differences in the behavior of each user who came to the library to seek information in order to realize their information needs. Keyword : information seeking behavior